Selection of the optimal culture conditions for high biomass synthesis by Trametes versicolor (Experimental biology, 2016)
Higher Basidiomycetes mushrooms are currently of interest because they are a rich source of various bioactive natural products. Mushrooms such as Ganoderma lucidum (Reishi), Lentinus edodes (Shiitake), Inonotus obliquus (Chaga), Trametes versicolor and many others have been collected and used for hundreds of years in Korea, China, Japan, and eastern Russia. In the case of the fungi of concern to this paper T. versicolor, commonly often called the "turkey tail", is a fungus which has been widely used through the centuries for the general promotion of health and longevity in Asian countries. T. versicolor has a long history of medical use, dating back hundreds of years. Subsequent research led to identification of two closely related proteoglycan constituents of T. versicolor with anticancer activity: Krestin (PSK) and polysaccharide peptide (PSP). Krestin (PSK) has been studied most extensively and is in wide clinical use as an adjunctive and adjuvant cancer therapy in Japan and China. This is a fungus which has been known to have numerous pharmacological effects including immunomodulating, anti-inflammatory, anti-cancer, anti-diabetic, anti-oxidative, radical-scavenging, and anti-aging effects. For most substances, fungal biomass obtained by submerged cultivation has higher nutritional value. The culture media in which mycelium grows is made of chemically pure and ecologically clean substances. In present study optimal culture conditions (composition of culture medium, temperature, pH, oxygen dissolution rate) for increased biomass synthesis in submerged culture have been studied. The objects of research work were strains of the fungus T. versicolor 353, 5095, 5131 used from the collection of mushrooms of the Institute of Botany named after N.G. Kholodny of the National Academy of Sciences of Ukraine. Investigation of the tested strains growth on nutrient media with different carbon and nitrogen sources revealed that the most appropriate source of nitrogen for all strains was peptone and the carbon – glucose. It was found that among all of strains tested the T. versicolor 353 is perspective strain for biomass and exopolysaccharides production when cultivated on glucose-peptone-yeast medium. The optimal ratio in production liquid medium C/N = 26,6. Under these conditions, strain T. versicolor 353 strain is able to synthesize in glucose -peptone-yeast medium up to 11.6 g / l of biomass. The optimal parameters of submerged cultivation of T. versicolor 353 strain for maximal accumulation of fungal biomass are as follows: temperature 30,0 ± 1,0 ° C, pH 5.0 ± 0.5, the oxygen dissolution rate (g О2 / l.h) - 0.55.
Keywords: Trametes versicolor; biologically active compounds; biomass; submerged cultivation; fungi.